Visible Light Effects on Photostrictive/Magnetostrictive PMN‐PT/Ni Heterostructure. Issue 36 (14th November 2022) - Dagur, Deepak; Polewczyk, Vincent; Petrov, Aleksandr Yu.; Carrara, Pietro; Brioschi, Marta; Fiori, Sara; Cucini, Riccardo; Rossi, Giorgio; Panaccione, Giancarlo; Torelli, Piero; Vinai, Giovanni
Abstract: The possibility of modifying the ferromagnetic response of a multiferroic heterostructure via fully optical means exploiting the photovoltaic/photostrictive properties of the ferroelectric component is an effective method for tuning the interfacial properties. In this study, the effects of 405 nm visible‐light illumination on the ferroelectric and ferromagnetic responses of (001) Pb(Mg1/3 Nb2/3 )O3 ‐0.4PbTiO3 (PMN‐PT)/Ni heterostructures are presented. By combining electrical, structural, magnetic, and spectroscopic measurements, how light illumination above the ferroelectric bandgap energy induces a photovoltaic current and the photostrictive effect reduces the coercive field of the interfacial magnetostrictive Ni layer are shown. Firstly, a light‐induced variation in the Ni orbital moment as a result of sum‐rule analysis of x‐ray magnetic circular dichroic measurements is reported. The reduction of orbital moment reveals a photogenerated strain field. The observed effect is strongly reduced when polarizing out‐of‐plane the PMN‐PT substrate, showing a highly anisotropic photostrictive contribution from the in‐plane ferroelectric domains. These results shed light on the delicate energy balance that leads to sizeable light‐induced effects in multiferroic heterostructures, while confirming the need of spectroscopy for identifying the physical origin of interface behavior. Abstract : By combining electrical, structural, magnetic, and spectroscopic measurements on a multiferroic Pb(Mg1/3 Nb2/3 )O3 ‐0.4PbTiO3 /Nickel heterostructure, the magnetic variations of the Ni layer to the photovoltaic and photostrictive effects on PMN‐PT under illumination are correlated.